2009
DOI: 10.1097/ccm.0b013e318192fe4f
|View full text |Cite|
|
Sign up to set email alerts
|

Activated protein C improves lipopolysaccharide-induced cardiovascular dysfunction by decreasing tissular inflammation and oxidative stress*

Abstract: These data suggest that APC improves cardiovascular function: 1) by modulating the endotoxin induced-proinflammatory/prooxidant state, 2) by decreasing endothelial/leukocyte interaction and 3) by favoring stabilization of the extracellular matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…To our knowledge, this is the first study reporting new vascular insight on the benefits of the ex vivo nonanticoagulant effect of rhAPC on endothelial dysfunction induced by LPS, which involves several related cellular mechanisms. As previously reported, rhAPC likely contributes in limiting the process of refractory vasoplegia in patients with septic shock (28) as well as in endotoxemic rats (30) . Hence, rhAPC is able to blunt iNOS expression and probably subsequent NO production, resulting in an improvement in PE curve-dose contractility.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…To our knowledge, this is the first study reporting new vascular insight on the benefits of the ex vivo nonanticoagulant effect of rhAPC on endothelial dysfunction induced by LPS, which involves several related cellular mechanisms. As previously reported, rhAPC likely contributes in limiting the process of refractory vasoplegia in patients with septic shock (28) as well as in endotoxemic rats (30) . Hence, rhAPC is able to blunt iNOS expression and probably subsequent NO production, resulting in an improvement in PE curve-dose contractility.…”
Section: Discussionmentioning
confidence: 61%
“…Recent animal (13,30,40) and human (28) studies have suggested that rhAPC may improve hemodynamic and vascular reactivity to catecholamines during septic states. However, much of our current knowledge concerning rhAPC vascular activity is still much debated, especially with respect to its nonanticoagulant properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, data from the PROWESS study demonstrated that the use of APC was associated with a quicker reduction in cardiovascular failure. Post-PROWESS investigative areas have been associated with a myriad of cellular studies [70] demonstrating that APC, through reactions mediated by the endothelial protein C receptor (EPCR) [71] and the effector receptor (protease activated receptor-1), acts directly on cells to exert multiple cytoprotective effects including: (a) downregulation of proinflammatory gene expression [72]; (b) anti-apoptotic activity [73]; (c) antioxidant properties; and (d) protection of endothelial barrier function [74]. Recent animal [75] and human [76] data have suggested that APC may improve both vascular and myocardial dysfunction and vascular reactivity to catecholamines during endotoxin and/or septic challenges.…”
Section: Activated Protein Cmentioning
confidence: 99%